Development of CMOS UHF RFID modulator and demodulator using DTMOST techniques - Teh, Ying Khai; Mohd Yasin, Faisal; Choong, Florence; Ibne Reaz, Mamun (2009)
Dynamic Threshold MOSFET (DTMOST) circuits were explored for UHF RFID modulator and demodulator applications. Performance gain, power consumption, area penalty and design considerations associated with the DTMOST designs were compared and contrasted against the traditional cells. A lowered voltage supply headroom and higher speed performance using same energy per switching are observed by trading off minimum 20% more die area compared to the traditional circuits. This is due to the extra routing metals and individual well required for each DTMOST device.